Assessing Gait Speed in Acutely Ill Older Patients Admitted to an Acute Care for Elders Hospital Unit - Ostir, Glenn V. (2012)
BACKGROUND: Assessment of mobility in geriatric hospital units relies primarily on subjective observation or patient self-reports. We objectively examined the gait speed of hospitalized older patients. METHODS: Prospective study of 322 patients 65 years or older admitted from the community to a geriatric hospital unit between March 2008 and October 2009. Associations of gait speed (in meters per second) and activities of daily living with length of stay and home discharge were examined in multivariable logistic and generalized linear regression models. RESULTS: In total, 206 of 322 patients completed the gait speed walk, with a mean gait speed of 0.53 m/s. A strong association was found between faster gait speed and shorter length of stay. Patients unable to complete the walk and patients having gait speeds of less than 0.40 m/s had significantly longer lengths of stay by 1.9 and 1.4 days, respectively, compared with patients having gait speeds of at least 0.60 m/s. Similarly, patients unable to complete the walk (odds ratio, 0.03; 95% CI, 0.003–0.21) and patients having gait speeds of less than 0.40 m/s (odds ratio, 0.07; 95% CI, 0.001–0.63) had significantly decreased odds of home discharge compared with patients having gait speeds of at least 0.60 m/s. Activities of daily living were less robust than gait speed in discriminating the risk of length of stay or home discharge. CONCLUSIONS: Gait speed is a clinically relevant indicator of functional status and is associated with important geriatric health outcomes, including length of stay and home discharge. Gait speed could be used to complement information obtained by self-reported activities of daily living.